THE EFFECT OF MUDHARABAH AND MUSYARAKAH FINANCING ON NET INCOME THROUGH REVENUE SHARING IN ISLAMIC BANKS IN INDONESIA - Laster Jujanwar Bancin; Irfan; Maya Sari (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
In general, problems that are often experienced by companies cannot be separated from the funds needed to finance its business. In meeting their needs, almost everything companies utilize banking services. One of them is sharia banking that channels funds in the form of financing, including mudharabah finance, and musyarakah financing in the hope that Islamic banks will receive profit sharing from these financing. In the case of repayment of financing disbursed by Islamic banks has the potential to risk the risk of traffic jams in repayment, so that it can affect earnings. The study aims to (1) analyze the effect of Mudharabah, Musyarakah Financing and Profit Sharing Funding on Net Profit partially and simultaneously on Islamic Banks listed on the IDX. (2) analyze the effect of mudharabah and musyarakah financing, using Path Analysis of Net Profit through Revenue Sharing Revenue at Islamic Banks. population in this study are all Sharia Banks Listed on the Indonesia stock exchange. Based on the results of the study, it is obtained (1) direct influence, namely, a) mudharabah financing does not significantly influence the Profit Sharing of 0.930, b) Musyarakah financing significantly influences the Profit Sharing of 0.000, c) mudharabah financing significantly influences the Net Profit equal to 0.034, d) Musyarakah financing significantly influences the Net Profit of 0.001, e) revenue sharing significantly influences the Net Profit of 0.000, (2) the indirect effect, namely, a) the effect of the Mudharabah financing coefficient on Net Profit through Profit Sharing.